(untitled) (Revista do Centro de Estudos Portugueses, 2010)
O objetivo do artigo é analisar alguns aspectos da caracterização da personagem Hélène, no filme O Convento (1995), de Manoel de Oliveira, comparando-a a personagem Précieuse, no livro As terras do risco (1994), de Agustina Bessa-Luís. Embora o filme tenha sido lançado em 1995, ele não é uma adaptação do livro. Este é um caso interessante na relação entre literatura e cinema. O argumento do romance originou o filme, mas são obras independentes. Em ambos, porém, busco mostrar como as protagonistas foram construídas a partir de referências às personagens de Helena de Tróia tanto de obras da literatura grega clássica como do Fausto, de Goethe. The aim of this article is to analyse some aspects of the characterization of the figure of Hélène in the film The Convent (1995), by Manoel de Oliveira, comparing her to the character Précieuse from the novel As terras do risco (Dangerous Lands, 1994) by Agustina Bessa-Luís. While the film was released in 1995, it is not an adaptation of the book, and this is an interesting case in the relationship between literature and cinema. The story of the novel formed the basis for the film, but they are independent works. In both, however, I seek to show how the protagonists were constructed from references to the character Helen of Troy, drawing as much from works of classical Greek literature as from Goethe’s Faust.